ABCs of IBM z/OS system programming. - Singh, Karan (IBM redbooks., 2014)
This resource is volume one of a 13-volume collection that provides an introduction to the z/OS operating system and the hardware architecture. Whether readers are beginners or experienced system programmers, the ABCs collection provides the inf.